A Recent Systematic Review Of Cervical Cancer Diagnosis: Detection And Classification - Wan Azani Mustafa; Nur Ain Alias; Mohd Aminuddin Jamlos; Hiam Alquran; Shahrina Ismail (Semarak Ilmu Publishing, 2024)
Indexed by Scopus/MyCite